Two new species of Satonius Endrödy-Younga from China and notes on the wing polymorphism of S. kurosawai Satô (Coleoptera: Myxophaga: Torridincolidae) - Hájek, Jiří; Yoshitomi, Hiroyuki; Fikáček, Martin; Hayashi, Masakazu; Jia, Feng-Long (Zootaxa, 2011)
Two new species of Torridincolidae from China, Satonius fui sp. nov. (Hubei) and S. jaechi sp. nov. (Fujian) are described, illustrated and compared with other species of the genus. The polymorphism of metathoracic wings was studied in the Japanese S. kurosawai (Satô, 1982), which macropterous form is presented here for the first time. In addition, new records of S. stysi Hájek & Fikáček, 2008 in China are also briefly mentioned.